Evolution of the Regulation of Covert Investigative Actions in the Criminal Justice Process - Lela Gudadze (European Scientific Journal, ESJ, 2026)
Covert investigative actions (CIAs) represent an essential instrument of modern criminal justice systems, enabling law enforcement authorities to obtain evidence that is often inaccessible through traditional investigative methods. At the same time, the intrusive nature of such measures raises significant concerns regarding the protection of fundamental human rights, particularly the right to privacy and procedural safeguards.This study examines the legal framework governing covert investigative actions in Georgia and evaluates its compatibility with European human rights standards. The research is based on qualitative legal methodology, combining doctrinal analysis of Georgian criminal procedural legislation with comparative analysis of selected foreign legal systems and relevant judicial practice, including the jurisprudence of the European Court of Human Rights.The findings indicate that Georgian legislation has undergone significant reforms aimed at strengthening judicial authorization, proportionality requirements, and data protection guarantees. Nevertheless, several key legal concepts remain insufficiently defined, including the notions of “legitimate purpose” and “urgent public need,” which may create interpretative ambiguities in practice.The paper argues that further legislative clarification, enhanced oversight mechanisms, and continuous professional training for law enforcement and judicial authorities are necessary to ensure that covert investigative measures are applied in full compliance with international human rights standards and the rule of law.